Tuning mechanical properties of seaweeds for hard capsules: A step forward for a sustainable drug delivery medium - Mohd Aiman, Hamdan; Khairatun Najwa, Mohd Amin; Rajan, Jose; Martin, Darren; Fatmawati, Adam (Elsevier B.V., 2021)
At present, vegetarian hard capsules from hydroxypropyl methyl cellulose is highly attractive to consumer market. However, the production volume is still low due to expensive raw polymer materials. Most of the renewable polymers do not meet sufficient mechanical strength for developing hard capsules. This work demonstrates that the mechanical properties of carrageenan, a sea-based edible material known as seaweeds, could be enhanced by the addition of small amounts (<2 wt./v%) of cellulose nanocrystals (CNC) for developing hard capsules. The microstructure and mechanical properties of the cellulose toughened carrageenan films are systematically correlated to the rheology of the solution from which the films were prepared. Carrageenan films containing 1.6 wt./v% of CNC showed an optimum viscosity of 1.17 mPas with 58% higher tensile strength than films without CNC. The hard capsules thereby developed are stable to three types of antibiotics, which are amoxycillin 500 mg, ampicillin 500 mg, and doxycycline 100 mg. The carrageenan biocomposite hard capsule is suitable for human consumption based on the cytotoxicity test on human body. All the hard capsule samples showed excellent disintegration behavior in physiological conditions. These achievements pose promising directions for sustainable materials supply for pharmaceutical industries.